2016
DOI: 10.1093/jac/dkw051
|View full text |Cite
|
Sign up to set email alerts
|

HIV virological failure and drug resistance in a cohort of Tanzanian HIV-infected adults

Abstract: High levels of early ART failure and drug resistance were observed among Tanzanian HIV-1-infected adults enrolled in a well-monitored study. Initiating treatment early and ensuring optimal adherence are vital for the success and durability of first-line ART in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
6
28
2
Order By: Relevance
“…paediatrics). Hawkins et al 21 reported a prevalence of 14.9% and 75.7% for virological failure and HIV-DRM, respectively, while studying a population in north-west Tanzania. A study conducted by Ngarina et al 22 in the city of Dar es Salaam, Tanzania, among women for 24 months post-partum, documented a proportion of virological failure of 61% at 12 months on ART, with drug resistance demonstrated in 34%.…”
Section: Discussionmentioning
confidence: 99%
“…paediatrics). Hawkins et al 21 reported a prevalence of 14.9% and 75.7% for virological failure and HIV-DRM, respectively, while studying a population in north-west Tanzania. A study conducted by Ngarina et al 22 in the city of Dar es Salaam, Tanzania, among women for 24 months post-partum, documented a proportion of virological failure of 61% at 12 months on ART, with drug resistance demonstrated in 34%.…”
Section: Discussionmentioning
confidence: 99%
“…A higher viral load may lead to HIV treatment failure, which is becoming a threat of different African countries, like in Burkina Faso (6.4%) [10], Ghana (15.7%) [11], and Tanzania (14.9%) [12]. In Ethiopia, virological, immunological, and clinical failure is found in the range between 1.3% [13] to 11.5% [14], 2.1% [15] to 21% [16], and 3.1% [17] to 12.3% [18], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A higher viral load may leads to HIV treatment failure, which is becoming a threat of different African countries, like in Burkina Faso (6.4%) (12), Ghana (15.7%) (13), and Tanzania (14.9%) (14). In Ethiopia, virological, immunological, and clinical failure found to be in the range between 1.3% (15) to 11.5% (16), 2.1% (17) to 21% (18), and 3.1% (19) to 12.3% (20) respectively.…”
Section: Introductionmentioning
confidence: 99%